(untitled) (Fiep Bulletin - online, 2015)
Leisure is an instrument that acts directly on the well being of life, once it is not only related to the laze, but also to the personal, social and physical development of the individual. The current study has the goal to analyze the leisure and physical activity, as relevant factors to the promotion of health and quality of life. We checked with the techniques adressed that the leisure and physical activity present a direct relation with the quality of life of individuals when compared with the ones that do not keep these practices. The way to achieve positive changes in the quality of life, may come from programs that stimulate the individual to seek a bigger achievement through leisure activities. Coming from this pressuposition, it is clear that leisure is a practice of fundamental importance to the promotion of health and increase in the quality of health.